A new and simple resonance Rayleigh scattering method for human serum albumin using graphite oxide as probe. (17th December 2012) - Wang, Shengmian; Xu, Lili; Wang, Lisheng; Liang, Aihui; Jiang, Zhiliang
ABSTRACT Graphite oxide (GO) was prepared by the Hummer procedure, and can be dispersed to stable colloid solution by ultrasonic wave. The GO exhibited an absorption peak at 313 nm, and a resonance Rayleigh scattering (RRS) peak at 490 nm. In pH 4.6 HAc‐NaAc buffer solution, human serum albumin (HSA) combined with GO probe to form large HSA‐GO particles that caused the RRS peak increasing at 490 nm. The increased RRS intensity was linear to HSA concentration in the range 0.50–200 µg/mL. Thus, a new and simple RRS method was proposed for the determination of HSA in samples, with a recovery of 98.1–104%. Copyright © 2012 John Wiley & Sons, Ltd.